KYAI MUAFI ALIF ZAINI, MODERNIZATION THOUGHTS AND MOVEMENTS FOR BOARDING BOARDING EDUCATIONAL INSTITUTIONS IN SAMPANG, MADURA - Madani, Mohammad Thoyyib; Rufaida, Rifki; Haris, Abd.; Zenrif, Fauzan; Barizi, Ahmad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Education and politics are two aspects that are closely related and intersect each other, so that both education and politics are indispensable in determining the characteristics of a country's education. Starting from the lack of appreciation of the future generations of the nation in the modern era for important figures who have contributed greatly to the development of education and politics, especially in Sampang Regency, it is a very important and unique issue to review. Therefore, this study aims to determine how the background, role and influence carried out by Kyai Mu'afi Alif Zaini in the world of education and politics in Sampang District in 1947 - 2006, there was also no complete biographical writing on this figure. The historical research method used in this research is divided into four parts, namely Heuristics (searching and finding data), criticism (source criticism), interpretation (interpretation), and historiography (writing history). The results showed that Kyai Muafi Alif Zaini is a scholar or community leader who was born on August 10, 1947 and died on January 27, 2006, he became a role model for the community because of his role and contribution in advancing education at the Nahzatut Thulab Islamic Boarding School in Sampang Regency. Among them were the driving force for the establishment of formal schools such as: MTs Nazhatut Thullab, SMP Nazhatut Thullab, MA Nazhatut Thullab, Nazhatut Thullab High School, Nazhatut Thullab Vocational School, IAI (Institut Agama Islam) Nazhatut Thullab, and STIKES Nazhatut Thullab so that the level of welfare in Sampang Regency has increased because it is based Comprehensive (PBB) and Cultural (PBKu). In addition, he was a cleric figure who was able to change the stigmatization of the Sampang people and the bad image of the Pilitik Party at that time